2019
DOI: 10.18805/ijar.b-3715
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Indian Mycoplasma gallisepticum isolates

Abstract: M. gallisepticum infection is a serious economic threat to the poultry industry in India, and the genetic diversity of Indian isolates is unknown. Gene-targeted sequence analysis of M. gallisepticum was conducted for the first time to map the diversity among different Indian isolates from different regions and from different clinical conditions. Sequence analysis of the mgc2 gene grouped the 13 field isolates into four groups. The most prevalent sequence type, the group1 shared 100% identity with the foreign s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our results showed close corroboration with Vaishali et al (2020) Rajkumar et al (2018) recorded 25.98% incidence of MS and 9.45% incidence of MG in the suspected dead birds. In their study, they found higher incidence of MS than that of MG.…”
Section: Prevalence Of Mssupporting
confidence: 89%
“…Our results showed close corroboration with Vaishali et al (2020) Rajkumar et al (2018) recorded 25.98% incidence of MS and 9.45% incidence of MG in the suspected dead birds. In their study, they found higher incidence of MS than that of MG.…”
Section: Prevalence Of Mssupporting
confidence: 89%
“…Infections with avian mycoplasma are becoming more common, and this has resulted in significant economic losses all over the world [25]. MS is a major contributor to 33% chicken mortality, causing infectious synovitis and asymptomatic upper respiratory tract infection [26]. The current analysis shows the prevalence of mycoplasma in several Egyptian governorates using both conventional and modern methods.…”
Section: Discussionmentioning
confidence: 92%
“…Mycoplasma have a very wide variety of hosts, namely small ruminants (Marenda et al 2005;Manimaran and Singh, 2018), cattle (Goswami et al 2019;Waseem et al 2020 ) Poultry (Manimaran and Singh, 2018;Rajkumar et al 2019). Contagious agalactia occurs in many parts of the world, especially in the Mediterranean and in Turkey (Amores et al 2011;Birben, 2020;Ozturkler and Otlu, 2020) Basin.…”
Section: Introductionmentioning
confidence: 99%